1983
DOI: 10.1111/j.1095-8312.1983.tb01590.x
|View full text |Cite
|
Sign up to set email alerts
|

Extending Darwin's investigations on the barnacle life-history

Abstract: Darwin's magnificent study of the stalked, sessile and fossil barnacles, perhaps his greatest work, was started not many years after the systematic position of cirripedes within the class Crustacea had been accepted. It was completed at a time when histology and microtomy were not developed and when living specimens could only be seen on occasional visits to the seaside. Yet 130 years later it remains the standard text.It was on a visit to Tenby that he observed that barnacles were sensitive to vibration and, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

1985
1985
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…A relationship between attachment site and sexuality can be explained by two possible proximate mechanisms: selective attachment by larvae with genetically predetermined sex, or environmental sex determination affected by the substratum type. Although sex determination among thoracican barnacles is largely unknown (Crisp ; Yusa et al. ), Callan () suggested that sex determination was environmental in Scalpellum scalpellum ( Linnaeus 1767), and Gomez () argued that it was genetic in Conopea galeata ( Linnaeus 1771).…”
Section: Discussionmentioning
confidence: 99%
“…A relationship between attachment site and sexuality can be explained by two possible proximate mechanisms: selective attachment by larvae with genetically predetermined sex, or environmental sex determination affected by the substratum type. Although sex determination among thoracican barnacles is largely unknown (Crisp ; Yusa et al. ), Callan () suggested that sex determination was environmental in Scalpellum scalpellum ( Linnaeus 1767), and Gomez () argued that it was genetic in Conopea galeata ( Linnaeus 1771).…”
Section: Discussionmentioning
confidence: 99%
“…Cyprid locomotion, exploration and settlement has been well documented (Knight-Jones 1953;Crisp 1983;Yule and Crisp 1983;Crisp 1985;Crisp 1990;Mullineaux and Butman 1991;Glenner and Hoeg 1993;Konya and Miki 1994;Miron et al 2000;Dahlstrom et al 2004) use their antennae to "walk" along a substrate until a suitable location is found to settle. Faimali et al (2004) found that barnacle cyprids may perceive signals about the substratum surface or its biofilm, which plays a role in their settlement preference.…”
Section: Barnacles: Intriguing Underwater Adhesionmentioning
confidence: 99%
“…As a consequence of this, through geological time, cirripedes evolved peculiar solutions to cope with the disadvantages of a sessile lifestyle. Their ability to adapt to different environmental pressures, especially in the intertidal environment (CRISP & BOURGET 1985), inspired Darwin his view of organic evolution (CRISP 1983). The earliest confirmed cirripede is of Silurian age, while the earliest known modern neobalanoform is of Late Cretaceous age (BUCKERIDGE & NEWMAN 2006;KOČÍ et al 2017).…”
Section: Introductionmentioning
confidence: 99%